Desenvolvimento territorial no Brasil: a experiência dos consórcios de segurança alimentar e desenvolvimento local - Jesus, Clesio Marcelino de (2006)
This dissertation studies the territorial development from a structural public politics implemented by government in the ambit of the Zero Famine Programme. Through this politics, the Alimentary Security Consortium end Social Development were installed (CONSADs). We started the discussion about Brazil development until get to the territorial dimension, and we deepen fundamental questions related to these spaces nand the globalization process, the civil spciety and public power participation, the rural urban dichotomy surpassing and discentralization by intermunicipal actions. In this study, we investigated the implementation of three CONSASD on the center west region and we could conclude that the government proposal is innovated and is capable of estimulate the territorial development. However, we still verified that this politics a collection of changers to improve it, mainly, when it is applied in depressed territorries.